2014
DOI: 10.1093/ptep/ptu101
|View full text |Cite
|
Sign up to set email alerts
|

A renormalization group method for studying the early universe in the Lorentzian IIB matrix model

Abstract: We propose a new method for studying the early universe in the Lorentzian version of the IIB matrix model, which is considered to be a nonperturbative formulation of superstring theory. This method is based on the idea of renormalization group, and it enables us to study the time-evolution of the universe for much longer time than in the previous work, which showed that the SO(9) rotational symmetry is spontaneously broken down to SO(3) after a "critical time". We demonstrate how this method works in a simplif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 73 publications
3
51
0
Order By: Relevance
“…In this way, it was found that only three out of nine directions start to expand at some critical time, which implies that the model predicts the emergence of a (3+1)d expanding space-time from superstring theory in (9+1)d. The expanding behavior for a longer time was investigated by simulating simplified models. The obtained results suggested a scenario for the full model that the expansion is exponential at early times [9], which is reminiscent of the inflation, and that it turns into a power law [10] at later times, which is reminiscent of the Friedmann-Robertson-Walker universe in the radiation dominated era. See also refs.…”
Section: Introductionmentioning
confidence: 82%
“…In this way, it was found that only three out of nine directions start to expand at some critical time, which implies that the model predicts the emergence of a (3+1)d expanding space-time from superstring theory in (9+1)d. The expanding behavior for a longer time was investigated by simulating simplified models. The obtained results suggested a scenario for the full model that the expansion is exponential at early times [9], which is reminiscent of the inflation, and that it turns into a power law [10] at later times, which is reminiscent of the Friedmann-Robertson-Walker universe in the radiation dominated era. See also refs.…”
Section: Introductionmentioning
confidence: 82%
“…The expanding behavior for a longer time was investigated by simulating the simplified models. The obtained results suggested a scenario for the full model that the expansion is exponential at early times [15], which is reminiscent of the inflation, and that it turns into a power law [16] at later times, which is reminiscent of the Friedmann-Robertson-Walker universe in the radiation dominated era. See also refs.…”
Section: Introductionmentioning
confidence: 82%
“…In ref. [2] and our subsequent work [15][16][17][18] on the Lorentzian type IIB matrix model and its simplified models, the sign problem was avoided by integrating out the scale factor of the bosonic matrices by hand, which yields a function of the bosonic action S b sharply peaked at the origin. Approximating this function by a sharply peaked Gaussian function, we can perform Monte Carlo simulations without the sign problem.…”
Section: Introductionmentioning
confidence: 99%
“…where we put L = 1 without loss of generality since the action is homogeneous in A µ and ψ (for details, see [4]), and we take the κ → ∞ limit as N → ∞. We can fix SU(N) symmetry A µ → UA µ U † where U ∈ SU(N).…”
Section: Lorentzian Modelmentioning
confidence: 99%
“…One is called the VDM model [4], and the other is called the bosonic model [5]. The former is expected to effectively describe the expanding behavior at early times, while the latter that at late times.…”
Section: Introductionmentioning
confidence: 99%